2023
DOI: 10.1097/jcn.0000000000000973
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Meditation Intervention on Self-management in Adult Patients With Type 2 Diabetes

Abstract: Background Diabetes complications are prevalent and cause adverse effects on the physical, psychological, and economic status of adult patients with type 2 diabetes. Meditation may positively affect self-management and, in turn, reduce diabetes complications. However, the systematic examination of the effects of meditation without additional components on self-management in this population have been rarely examined. Purpose The aim of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
(290 reference statements)
0
4
0
Order By: Relevance
“…Heo et al [ 42 ] assessed the effects of meditation on self-management in people with type 2 diabetes. A total of nine RCTs (10 articles) with 698 subjects were included in the analysis [ 17 , 19 , 31 , 32 , 36 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Heo et al [ 42 ] assessed the effects of meditation on self-management in people with type 2 diabetes. A total of nine RCTs (10 articles) with 698 subjects were included in the analysis [ 17 , 19 , 31 , 32 , 36 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…This approach should involve interventions such as meditation, improving sleep patterns, cultivating social support networks, and providing psychological support. [21][22][23][24] Recognizing the need for these interventions is crucial in effectively managing diabetes.…”
Section: Tablementioning
confidence: 99%
“…One systematic review and meta-analysis study was conducted to assess the effects of meditation interventions on the self-management of people with T2D. It found that mindfulness-based meditation reduced hemoglobin A1c levels but not fasting blood sugar levels [120]. There were problems with the randomization in some studies and with missing information about the results.…”
Section: Meditationmentioning
confidence: 99%
“…There were problems with the randomization in some studies and with missing information about the results. Variations in the duration of follow-up, group size, and measured outcomes were prominent among the included studies [120].…”
Section: Meditationmentioning
confidence: 99%